Social security for special categories of disabled people in the Ukrainian SSRin the 1920s. - Olha Murashova; Yurii Zinko (Наукові записки Вінницького державного педагогічного університету імені Михайла Коцюбинського. Серія: Історія)
The article is aimed at studying and analyzing the practical experience of the activities of state authorities in implementing the policy of social security for the disabled in the 1920s. The methodological basis of the study is the fundamental principles of historical research: historicism, consistency, objectivity in the course of working with documents. Among the special methods used in the study should be called problem-chronological, historical-systemic, historical-typological. The scientific novelty of the article is to highlight the features of state policy on the organization of social security of special categories of disabled. Conclusions. Having seized power on the territory of Ukraine, the Bolshevik government publicly announced its intentions to create an effective system of social security for the disabled strata of society. Material support for a special category of disabled people was assigned exclusively to the state. However, under the conditions of the new economic policy with its market principles, a small number of people could count on security. At the same time, despite the low size of social payments, the very fact of her appointment, the Soviet authorities tried to testify their value to the proletarian state. Social protection of special categories of the disabled, which included the Red Army, the disabled of the World War І and the Civil War, family members of the dead military, persons who had special merits before the Soviet state, was carried out by the People's Commissariat of Social Security through its departments on the ground at the expense of the state budget. Due to its limited volume, the amount of social payments was significantly inferior to payments made at the expense of insurance premiums.